The assessment of metacognition in children aged 4–16 years: a systematic review. Issue 1 (30th May 2016) - Gascoine, Louise; Higgins, Steve; Wall, Kate
Abstract : This article presents the results of a systematic review of methods that have been used to measure or assess metacognition in children aged 4–16 years over a 20‐year period (1992–2012). It includes an overview of the types of tool and methods used linked with the ages of the participants targeted and how metacognition and associated concepts are defined. Two thousand, seven hundred and twenty‐one records were identified through systematic searching; 525 articles or reports were full text screened, resulting in 149 included studies reporting 84 distinct tools or methods. Of these 84 distinct tools or methods, four were excluded from further analysis after appraisal for reliability, validity and replicability. The final number of methods and tools for metacognitive assessment included in the analysis is 80. The key findings of this review include: Self‐report measures (including questionnaires, surveys and tests) comprise 61% of the included tools; Observational methods that do not rely on prompting to 'think aloud' (Think Aloud Protocols) have only been used with students aged 9 years and under; Information about reliability and validity is not always given or given accurately for different tools and methods; The definition of metacognition in a particular study relates directly to its assessment and therefore its outcomes: this can be misaligned.